God of war [videorecording (DVD)] - Chen, Jiashang; Chen, Jiashang; Zhao, Wenzhuo, 1972-; Hung, Samo, 1952-; Kurata, Yasuaki (Well Go USA, 2017)
In the sixteenth century in China, a commander and his newly promoted general devise a plan to rid the country's coastline of pirates.